Schleppende deutsche Exportentwicklung: zyklisch oder strukturell? - Heiko Peters; Stefan Schneider (Wirtschaftsdienst, 2015)
Der Welthandel wächst seit 2012 anders als in den vergangenen Jahrzehnten schwächer als das globale Bruttoinlandsprodukt. Diese Entkopplung deutet auf strukturelle Veränderungen hin. Besonders die deutschen Exporte sind von dieser Entwicklung betroffen und dürften daher auch in den nächsten Jahren nur verhalten wachsen. – – After world trade slumped in 2009 due to the global financial crisis, it rebounded strongly in 2010 and 2011. Since 2012, however, global trade growth has been anaemic and, in contrast to past decades, has been even lower than global GDP growth. The little momentum generated since 2012 points towards structural changes which effect German exports especially negatively. Therefore, German export growth should be relatively muted in the coming years. The authors forecast average real German export growth at the lower end of a range of 4% -6% between 2014 and 2019, despite being buttressed by a depreciation of the euro.
Keywords: F10; F60; J30; 330; Internationale Wirtschaft; Export; Deutschland